A construção da subjetividade dos atores em letras de canções de João Bosco e Aldir Blanc - Boutelet, Vinícius de Almeida (2013)
This work has used French Semiotics theoretical framework to analyze four lyrics of João Bosco and Almir Blanc’s songs. We aimed at describing actor’s subjectivity which are revealed in these lyrics. We have resorted to elements systematized by Algirdas Julien Greimas and Joseph Courtés, Jacques Fontanille and divulged by Brazilian semioticists Diana Luz Pessoa de Barros and José Luiz Fiorin whose titles we have also resorted to. We have applied elements of the meaning generative process and some aspects of Semiotics of passion on the texts in order to describe male and female actors fulfilled on them. Their actantial roles associated to the narrative level, their thematic roles associated to the discoursive level and their pathematic roles regarding their states of soul were observed. Our corpus is constituted by the lyrics of the songs “Dois pra lá, dois pra cá”, “Incompatibilidade de gênios”, “Miss Suéter” and “Feminismo no Estácio” in which male and female actors are manifested. These actors’ involvement is established by contractual or controversial relations by which they have their subjectivity revealed. Key words: French semiotics; actor; subjectivity; passion; João Bosco and Aldir Blanc.